2019
DOI: 10.1103/physreve.99.022408
|View full text |Cite
|
Sign up to set email alerts
|

Role of geometrical cues in neuronal growth

Abstract: Geometrical cues play an essential role in neuronal growth. Here, we quantify axonal growth on surfaces with controlled geometries and report a general stochastic approach that quantitatively describes the motion of growth cones. We show that axons display a strong directional alignment on micro-patterned surfaces when the periodicity of the patterns matches the dimension of the growth cone. The growth cone dynamics on surfaces with uniform geometry is described by a linear Langevin equation with both determin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(90 citation statements)
references
References 35 publications
5
74
1
Order By: Relevance
“…In our previous work, we have shown that axonal growth on surfaces with controlled geometries arises as the result of an interplay between deterministic and stochastic components of growth cone motility [ 10 , 15 , 16 , 19 , 20 ]. Deterministic influences include, for example, the presence of preferred directions of growth along specific geometric patterns on substrates, while stochastic components come from the effects of polymerization of cytoskeletal elements (actin filaments and microtubules), neuron signaling, low concentration biomolecule detection, biochemical reactions within the neuron, and the formation of lamellipodia and filopodia [ 1 , 2 , 7 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous work, we have shown that axonal growth on surfaces with controlled geometries arises as the result of an interplay between deterministic and stochastic components of growth cone motility [ 10 , 15 , 16 , 19 , 20 ]. Deterministic influences include, for example, the presence of preferred directions of growth along specific geometric patterns on substrates, while stochastic components come from the effects of polymerization of cytoskeletal elements (actin filaments and microtubules), neuron signaling, low concentration biomolecule detection, biochemical reactions within the neuron, and the formation of lamellipodia and filopodia [ 1 , 2 , 7 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deterministic influences include, for example, the presence of preferred directions of growth along specific geometric patterns on substrates, while stochastic components come from the effects of polymerization of cytoskeletal elements (actin filaments and microtubules), neuron signaling, low concentration biomolecule detection, biochemical reactions within the neuron, and the formation of lamellipodia and filopodia [ 1 , 2 , 7 , 21 ]. The resultant growth cannot be predicted for individual neurons due to this stochastic-deterministic interplay, however, the growth dynamics for populations of neurons can be modeled by probability functions that satisfy a set of well-defined stochastic differential equations, such as Langevin and Fokker–Planck equations [ 10 , 15 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In previous work, we have shown that axonal dynamics on uniform glass surfaces is described by an Ornstein-Uhlenbeck (OU) process, defined by a linear Langevin equation and stochastic white noise [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, devices fabricated at the microscale provide the remarkable advantage of precise experimental validation against analytical models of molecular and convective transport [41,42], viscoelasticity [43][44][45], electrochemical dynamics [46,47] and many others [48][49][50][51][52]. These advantages have pioneered the development of single and multiplexed microfluidic channels [53][54][55], micropatterned substrate surfaces [56][57][58][59], and three-dimensional (3D) microfabricated structures [60,61] to examine localized cell behavior. Moreover, microfluidic "upgrades" of conventional bioassays, such as culture flasks and chambers, have significantly enriched abilities to examine cell behavior on the in vivo microscale.…”
Section: Characteristics Of Microfluidicsmentioning
confidence: 99%